Positive electrode material and preparation method and application thereof
By forming a VPO5 cladding layer on the surface of the positive electrode material, the problems of unstable structure of the positive electrode material and the complex process and high cost of existing modification methods are solved, and the effect of improving the battery magnification and cycling performance is achieved.
Patent Information
- Application Number
- CN202311407486.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
AI Technical Summary
The structure of the cathode material of lithium-ion batteries is unstable during the cycle process, which affects the cycle life and rate performance of the battery. The existing coating modification methods have problems such as complex process and high cost.
By dispersing the positive electrode active material, surfactant and solvent, vanadium source material and phosphorus source material are added, and after drying and high temperature calcining, a positive electrode material with a VPO5 coating layer is formed.
It improves the interface stability of the positive electrode material, reduces side reactions and dissolution of transition metal ions, maintains the structural stability of the material, accelerates the diffusion of lithium ions, reduces surface polarization and impedance, and improves magnification and cycling performance.
Smart Images

Figure CN119905533A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a positive electrode material and a preparation method and application thereof. Background Art
[0002] With the progress of society and the continuous development of science and technology, people hope to develop lithium-ion batteries with higher energy density and power density to achieve longer battery life and energy storage. However, common lithium-ion battery cathode materials, such as lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), lithium iron phosphate (LiFePO4), ternary materials (NCM, NCA), etc., are structurally unstable during the cycle process, have serious side reactions with electrolytes, and have problems such as structural collapse, microcrack formation, and active material dissolution, which greatly damage the battery's cycle life and rate performance.
[0003] At present, researchers mainly use surface modification methods such as doping, coating, and structural design. Surface modification can enhance the surface stability of positive electrode materials, improve ion and electron conductivity, reduce interfacial charge transfer impedance, and reduce side reactions, thereby effectively improving the electrochemical performance of positive electrode materials under specific conditions. Among them, surface coating is considered to be a more effective and economical method because it not only improves the capacity retention rate and rate performance, but also improves the thermal stability of positive electrode materials. There are two main structures of surface coating modified materials: one is to coat the surface of the positive electrode with nanometer thickness of heterogeneous materials, and the other is to coat the surface of the positive electrode with different interlayer materials to form a composite material. The surface coating layer can reduce the direct contact between the active material and the electrolyte. Commonly used surface coating methods include sol-gel method, hydrothermal / solvothermal method, coprecipitation method, solid phase method, chemical vapor deposition (CVD), atomic layer deposition (ALD), etc. At present, carbon materials, metal oxides, fluorides, phosphates, electrode materials, solid electrolytes and other ion conductors, conductive polymers, etc. are more commonly used for surface modification of positive electrode materials.
[0004] However, the above modification methods all have certain shortcomings. For example, the hydrothermal / solvothermal method is complex, costly and has low yield; the solid phase method makes it difficult to obtain a uniform coating layer; the vapor deposition method has low yield, long time, high cost and may be toxic.
[0005] Therefore, developing an economical and efficient surface modification method to obtain positive electrode materials with excellent performance is of great significance for the development of positive electrode materials for lithium-ion batteries. Summary of the invention
[0006] The purpose of the present invention is to provide a positive electrode material and its preparation method and application, so as to solve the problem that the positive electrode material is structurally unstable during the cycle process, affecting the cycle life and rate performance of the battery, as well as the existing coating and modification methods for the positive electrode material, which have complex processes and high costs.
[0007] To this end, in a first aspect, an embodiment of the present invention provides a method for preparing a positive electrode material, the preparation method comprising:
[0008] Placing the positive electrode active material, the surfactant and the solvent in a dispersing device for dispersing treatment and mixing them uniformly to obtain a first solution;
[0009] Adding the vanadium source material and the phosphorus source material to the first solution, continuing the dispersion treatment, and mixing evenly to obtain a second solution;
[0010] placing the second solution in a drying device for drying to obtain a precursor material;
[0011] The precursor material is placed in a high-temperature device for calcination, so that the surface of the particles of the above-mentioned positive electrode active material is coated with VPO5, and naturally cooled to room temperature to finally obtain the positive electrode material.
[0012] Preferably, the positive electrode active material includes: any one of lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium iron phosphate, nickel cobalt manganese, nickel cobalt aluminum ternary material, and lithium-rich manganese-based positive electrode material; the particle size of the positive electrode active material is 0.5 μm-20 μm;
[0013] The surfactant includes one or more of sodium stearate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, octadecyltrimethylammonium chloride, polyacrylamide, lecithin, glyceryl monostearate, fatty acid glyceride or polysorbate;
[0014] The mass percentage of the surfactant to the mass percentage of the positive electrode active material is 0.05%-3%. Preferably, the solvent is a mixture of deionized water and anhydrous ethanol, wherein the volume ratio of deionized water to anhydrous ethanol is 1:[1-3];
[0015] The solid content of the first solution is 10 g / L-300 g / L.
[0016] Preferably, the vanadium source material includes: vanadium pentoxide and / or ammonium metavanadate; the phosphorus source material includes: one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate;
[0017] The molar ratio of vanadium in the vanadium source material to phosphorus in the phosphorus source material is 1:1.
[0018] Preferably, the dispersing equipment includes: one or more of an ultrasonic disperser, a mechanical stirring disperser, and a mixing disperser; and the dispersing treatment time is 12 minutes to 2 hours.
[0019] Preferably, the drying equipment includes: one or more of a vacuum dryer, a box dryer, a spray dryer, a microwave dryer, an infrared dryer, a fluidized bed dryer, and an air flow dryer;
[0020] The drying treatment includes: any one of normal pressure drying, reduced pressure drying, spray drying, microwave drying, and infrared drying; the temperature of the drying treatment is 40°C-120°C.
[0021] Preferably, the high temperature equipment includes: any one of a tube furnace, a box furnace, and a rotary furnace;
[0022] The specific conditions of the calcination are: the calcination temperature is 450°C-650°C, the heating rate is 2°C / min-10°C / min, the calcination time is 2 hours-6 hours, and the calcination atmosphere is any one of dry air, nitrogen and argon.
[0023] In a second aspect, an embodiment of the present invention provides a positive electrode material prepared by the preparation method described in the first aspect, wherein the positive electrode material comprises a positive electrode active material and a VPO5 coating layer coated on the outer surface of the positive electrode active material;
[0024] The VPO5 coating layer is a continuous thin film with a thickness of 2nm-5nm;
[0025] The positive electrode active material includes: any one of lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium iron phosphate, nickel cobalt manganese, nickel cobalt aluminum ternary material, and lithium-rich manganese-based positive electrode material;
[0026] The mass percentage of the VPO5 coating layer to the mass percentage of the positive electrode active material is 0.1%-5%.
[0027] In a third aspect, an embodiment of the present invention provides a positive electrode plate, which includes a positive electrode material prepared by any preparation method described in the first aspect, or the positive electrode material described in the second aspect.
[0028] In a fourth aspect, an embodiment of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet described in the third aspect.
[0029] The embodiment of the present invention provides a positive electrode material and a preparation method and application thereof, wherein a positive electrode active material and a surfactant are dissolved in a solvent, a vanadium source material and a phosphorus source material are then added, and the positive electrode material is finally obtained after drying and high-temperature calcination. The structure of the positive electrode material of the present invention is that a VPO5 coating layer is formed on the surface of the positive electrode active material, wherein VPO5 has the advantages of large-size channels for rapid lithium ion transmission and zero volume change in electrochemical behavior, which can not only improve the interface stability between the electrode and the electrolyte, effectively avoid direct contact between the electrode and the electrolyte, reduce the occurrence of side reactions, inhibit the dissolution of transition metal ions, and maintain the structural stability of the material, but also accelerate the diffusion of lithium ions, reduce surface polarization and impedance, and improve the rate and cycle performance of the positive electrode material. The positive electrode material of the present invention is applied to lithium-ion batteries to improve the rate performance and cycle stability of the battery.
[0030] The preparation method provided by the embodiment of the present invention is simple to operate, low in cost and high in efficiency, and can be applied to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.
[0032] Figure 1 It is a flow chart of the method for preparing the positive electrode material provided in an embodiment of the present invention.
[0033] Figure 2 It is a charge and discharge curve diagram of button batteries assembled in Example 1 of the present invention and Comparative 1.
[0034] Figure 3 It is a cycle capacity curve diagram of button batteries assembled in Example 1 of the present invention and Comparative 1.
[0035] Figure 4 It is a charge and discharge curve diagram of button batteries assembled in Example 2 of the present invention and Comparative 2.
[0036] Figure 5 It is a cycle capacity curve diagram of button batteries assembled in Example 2 of the present invention and Comparative 2.
[0037] Figure 6 It is a charge and discharge curve diagram of button batteries assembled in Example 3 of the present invention and Comparative 3.
[0038] Figure 7 It is a cycle capacity curve diagram of button batteries assembled according to Example 3 of the present invention and Comparative 3.
[0039] Figure 8 This is an X-ray diffraction (XRD) diagram of the solid material prepared in Example 6 of the present invention. DETAILED DESCRIPTION
[0040] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.
[0041] The present invention provides a method for preparing a positive electrode material. Figure 1 As shown, the preparation method comprises:
[0042] Step 110, placing the positive electrode active material, the surfactant and the solvent in a dispersion device for dispersion treatment, and mixing them uniformly to obtain a first solution;
[0043] The positive electrode active material includes: any one of lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium iron phosphate, nickel cobalt manganese, nickel cobalt aluminum ternary material, and lithium-rich manganese-based positive electrode material; the particle size of the positive electrode active material is 0.5 μm-20 μm;
[0044] The surfactant includes one or more of sodium stearate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, octadecyltrimethylammonium chloride, polyacrylamide, lecithin, glyceryl monostearate, fatty acid glyceride or polysorbate; the mass percentage of the surfactant to the mass percentage of the positive electrode active material is 0.05%-3%; the addition of the surfactant in the present invention can make the particles of the positive electrode active material disperse more evenly in the solution, and in addition, the functional groups in the surfactant molecules can adsorb related ions on the surface of the particles of the positive electrode active material in the subsequent coating, which is conducive to the subsequent coating;
[0045] The solvent is a mixture of deionized water and anhydrous ethanol, wherein the volume ratio of deionized water to anhydrous ethanol is 1:[1-3]; the present invention adopts a mixed solvent of deionized water and anhydrous ethanol because the mixed solvent has better solubility.
[0046] The solid content of the first solution is 10g / L-300g / L;
[0047] The dispersion equipment includes: one or more of an ultrasonic disperser, a mechanical stirring disperser, and a mixing disperser; and the dispersion treatment time is 12 minutes to 2 hours.
[0048] Step 120, adding the vanadium source material and the phosphorus source material to the first solution, continuing the dispersion treatment, and mixing them uniformly to obtain a second solution;
[0049] The vanadium source material includes: vanadium pentoxide and / or ammonium metavanadate; the phosphorus source material includes: one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate;
[0050] The molar ratio of vanadium in the vanadium source material to phosphorus in the phosphorus source material is 1:1.
[0051] Step 130, placing the second solution in a drying device for drying to obtain a precursor material;
[0052] The drying equipment includes: one or more combinations of vacuum dryers, box dryers, spray dryers, microwave dryers, infrared dryers, fluidized bed dryers, and air flow dryers;
[0053] The drying treatment includes: any one of normal pressure drying, reduced pressure drying, spray drying, microwave drying, and infrared drying; the temperature of the drying treatment is 40°C-120°C.
[0054] Step 140, placing the precursor material in a high temperature device for calcination, so that the surface of the particles of the positive electrode active material is coated with VPO5, and naturally cooling to room temperature, finally obtaining the positive electrode material;
[0055] The high temperature equipment includes any one of a tube furnace, a box furnace, and a rotary furnace;
[0056] The specific conditions of calcination are as follows: the calcination temperature is 450°C-650°C, the heating rate is 2°C / min-10°C / min, the calcination time is 2 hours-6 hours, and the calcination atmosphere is any one of dry air, nitrogen, and argon.
[0057] The positive electrode material prepared by the above-mentioned preparation method in the embodiment of the present invention includes a positive electrode active material and a VPO5 coating layer coated on the outer surface of the positive electrode active material;
[0058] The VPO5 coating layer is a continuous film with a thickness of 2nm-5nm;
[0059] The positive electrode active material includes: any one of lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium iron phosphate, nickel cobalt manganese, nickel cobalt aluminum ternary material, and lithium-rich manganese-based positive electrode material;
[0060] The mass percentage of the VPO5 coating layer to the mass percentage of the positive electrode active material is 0.1%-5%.
[0061] The positive electrode material in the embodiment of the present invention can be used as a positive electrode active material to prepare a positive electrode plate, and the positive electrode plate is applied to a lithium-ion battery to improve the specific capacity and cycle performance of the battery.
[0062] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the positive electrode material of the present invention are respectively described below with multiple specific examples.
[0063] Example 1
[0064] This embodiment provides a preparation process and performance test of a positive electrode material, and the specific process is as follows:
[0065] (1) 0.5 g of sodium dodecyl sulfate was dissolved in 500 mL of deionized water and anhydrous ethanol, wherein the volume ratio of deionized water to anhydrous ethanol was 1:2, 20 g of lithium cobaltate was added, and the mixture was stirred for 0.5 hour, and then ultrasonically dispersed in an ultrasonic disperser for 0.2 hour to obtain a first solution.
[0066] (2) 0.289 g of ammonium metavanadate and 0.326 g of diammonium hydrogen phosphate were added to the first solution, and the dispersion treatment was continued for 1 hour. The mixture was mixed to obtain a second solution.
[0067] (3) The second solution was placed in a box dryer and vacuum dried at 90° C. to obtain a precursor material.
[0068] (4) The precursor material is placed in a tube furnace, heated to 600°C at 5°C / min in a dry air atmosphere, and calcined for 4 hours so that the surface of the particles of the above-mentioned positive electrode active material is coated with VPO5, and then naturally cooled to room temperature to finally obtain the positive electrode material.
[0069] The positive electrode material prepared in this embodiment was used to prepare a positive electrode sheet and assembled into a CR2032 button battery for testing. The specific process is as follows.
[0070] The specific preparation process of the positive electrode sheet is as follows: the positive electrode material, conductive carbon black and polyvinylidene fluoride (PVDF) prepared above are weighed and mixed evenly in a mass ratio of 8:1:1, N-methylpyrrolidone (NMP) solution is added, and the positive electrode slurry is obtained by stirring. Then, the positive electrode slurry is evenly applied on an aluminum foil using a coating machine, and the electrode sheet is obtained by drying at 80°C for 12 hours. The electrode sheet is cut into discs with a diameter of 12 mm, and the loading amount of active material on each disc is about 2-3 mg / cm 2 , and obtain the positive electrode.
[0071] The specific process of assembling the battery is as follows: in a glove box filled with argon, the positive electrode sheet prepared as above is used, the metal lithium sheet is used as the negative electrode sheet, a Celgard 2500 diaphragm is used, the solute is LiPF6 with a concentration of 1 mol / L, and the solvent is an organic mixture of ethylene carbonate (EC) / dimethyl carbonate (DMC) (the volume ratio of EC to DMC is 1:1) as the electrolyte, and assembled into a CR2032 button battery.
[0072] Battery testing process: The battery was left to stand for 8 hours at room temperature with a charging voltage of 4.5V and a discharge cut-off voltage of 3V. A constant current charge and discharge cycle test was performed on a Blue Power battery testing system (CT2001A). The charge and discharge curves of the battery assembled in this embodiment were tested. Figure 2 As shown; Cycle capacity curve, such as Figure 3The first week charge capacity at 0.1C current density was 214.6 mAh / g and the discharge capacity was 196.4 mAh / g. The capacity retention rate after 100 cycles at 0.2C current density was 86.7%.
[0073] Comparative Example 1
[0074] The lithium cobalt oxide in Example 1 was used directly as the positive electrode active material without being treated to assemble a CR2032 button cell and test it. The assembly process and test method were the same as those in Example 1.
[0075] The charge and discharge curves of the battery assembled in this comparative example are as follows: Figure 2 As shown; Cycle capacity curve, such as Figure 3 As shown. The first week charge capacity at 0.1C current density is 202.3mAh / g and the discharge capacity is 183.3mAh / g, and the capacity retention rate after 100 cycles at 0.2C current density is 52.8%. It can be seen that the first week charge and discharge capacity and the capacity retention rate after 100 cycles of the button cell with the positive electrode sheet containing positive electrode material in Example 1 are better than those in Comparative Example 1.
[0076] Example 2
[0077] This embodiment provides a preparation process and performance test of a positive electrode material, and the specific process is as follows:
[0078] (1) 0.8 g of octadecyltrimethylammonium chloride was dissolved in 600 mL of deionized water and anhydrous ethanol, wherein the volume ratio of deionized water to anhydrous ethanol was 1:3, 50 g of lithium iron phosphate was added, and the mixture was stirred for 0.4 hour, and then ultrasonically dispersed in an ultrasonic disperser for 0.2 hour to obtain a first solution.
[0079] (2) 0.361 g of ammonium metavanadate and 0.356 g of ammonium dihydrogen phosphate were added to the first solution, and the dispersion treatment was continued for 2 hours. The mixture was mixed to obtain a second solution.
[0080] (3) The second solution was placed in a spray dryer and spray-dried at 100° C. to obtain a precursor material.
[0081] (4) The precursor material is placed in a tubular furnace, heated to 650°C at 4°C / min in a nitrogen atmosphere, and calcined for 3 hours so that the surface of the particles of the above-mentioned positive electrode active material is coated with VPO5, and then naturally cooled to room temperature to finally obtain the positive electrode material.
[0082] The positive electrode material prepared in this embodiment is used to prepare positive electrode plates and assembled into CR2032 button batteries. The battery assembly process is the same as that in Example 1.
[0083] Battery testing process: The battery was left to stand for 8 hours at room temperature with a charging voltage of 4.2V and a discharge cut-off voltage of 2.5V. A constant current charge and discharge cycle test was performed on a Blue Power battery testing system (CT2001A). The charge and discharge curves of the battery assembled in this embodiment were tested. Figure 4 As shown; Cycle capacity curve, such as Figure 5 The first week charge capacity at 0.1C current density is 186.8mAh / g and the discharge capacity is 182.2mAh / g. The capacity retention rate after 500 cycles at 5C current density is 89.7%.
[0084] Comparative Example 2
[0085] The lithium iron phosphate in Example 2 was used directly as the positive electrode active material without being treated to assemble a CR2032 button battery and perform a test. The assembly process and the test method were the same as those in Example 2.
[0086] The charge and discharge curves of the battery assembled in this comparative example are as follows: Figure 4 As shown; Cycle capacity curve, such as Figure 5 As shown. The first week charge capacity at 0.1C current density is 178.3mAh / g and the discharge capacity is 174.2mAh / g, and the capacity retention rate after 500 cycles at 5C current density is 82.3%. It can be seen that the first week charge and discharge capacity and the capacity retention rate after 500 cycles of the button cell with the positive electrode material in Example 2 are better than those in Comparative Example 2.
[0087] Example 3
[0088] This embodiment provides a preparation process and performance test of a positive electrode material, and the specific process is as follows:
[0089] (1) 0.2 g of polyacrylamide was dissolved in 200 mL of deionized water and anhydrous ethanol, wherein the volume ratio of deionized water to anhydrous ethanol was 1:2, and 40 g of lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2, first stir for 1 hour, and then place it in an ultrasonic disperser for ultrasonic dispersion for 0.2 hour to disperse and mix it evenly to obtain the first solution.
[0090] (2) 0.578 g of ammonium metavanadate and 0.652 g of diammonium hydrogen phosphate were added to the first solution, and the dispersion treatment was continued for 2 hours. The mixture was mixed to obtain a second solution.
[0091] (3) The second solution is placed in a box dryer and heated and dried at 80° C. under normal pressure to obtain a precursor material.
[0092] (4) The precursor material is placed in a tube furnace, and the temperature is raised to 500°C at 3°C / min in an argon atmosphere, and calcined for 6 hours so that the surface of the particles of the above-mentioned positive electrode active material is coated with VPO5. The material is naturally cooled to room temperature to finally obtain the positive electrode material.
[0093] The positive electrode material prepared in this embodiment is used to prepare positive electrode plates and assembled into CR2032 button batteries. The battery assembly process is the same as that in Example 1.
[0094] Battery testing process: The battery was left to stand for 8 hours at room temperature with a charging voltage of 4.8V and a discharge cut-off voltage of 2V. A constant current charge and discharge cycle test was performed on a Blue Power battery testing system (CT2001A). The charge and discharge curves of the battery assembled in this embodiment were tested. Figure 6 As shown; Cycle capacity curve, such as Figure 7 The first week charge capacity at 0.1C current density is 337.6 mAh / g and the discharge capacity is 289.8 mAh / g. The capacity retention rate after 100 cycles at 0.2C current density is 87.5%.
[0095] Comparative Example 3
[0096] Using the lithium-rich manganese-based positive electrode material Li in Example 2 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 was directly used as the positive electrode active material without treatment to assemble into CR2032 button cells and tested. The assembly process and testing method were the same as those in Example 3.
[0097] The charge and discharge curves of the battery assembled in this comparative example are as follows: Figure 6 As shown; Cycle capacity curve, such as Figure 7 As shown. The first week charge capacity at 0.1C current density is 178.3mAh / g and the discharge capacity is 174.2mAh / g, and the capacity retention rate after 100 cycles at 0.2C current density is 66.9%. It can be seen that the first week charge and discharge capacity and the capacity retention rate after 100 cycles of the button cell with the positive electrode sheet containing positive electrode material in Example 3 are better than those in Comparative Example 3.
[0098] Example 4
[0099] This embodiment provides a preparation process and performance test of a positive electrode material, and the specific process is as follows:
[0100] (1) 0.12 g of octadecyltrimethylammonium chloride was dissolved in 600 mL of deionized water and anhydrous ethanol, wherein the volume ratio of deionized water to anhydrous ethanol was 1:1, 60 g of lithium manganate was added, and the mixture was stirred for 0.4 hour, and then ultrasonically dispersed in an ultrasonic disperser for 0.2 hour to obtain a first solution.
[0101] (2) 0.337 g of vanadium pentoxide and 0.363 g of phosphoric acid were added to the first solution, and the dispersion treatment was continued for 1.5 hours. The mixture was mixed to obtain a second solution.
[0102] (3) The second solution was placed in a microwave dryer and dried by microwave at 60° C. to obtain a precursor material.
[0103] (4) The precursor material is placed in a tube furnace, and the temperature is raised to 630° C. at a rate of 5° C. / min in a dry air atmosphere, and calcined for 4 hours so that the surface of the particles of the above-mentioned positive electrode active material is coated with VPO5. The precursor material is naturally cooled to room temperature to finally obtain the positive electrode material.
[0104] Example 5
[0105] This embodiment provides a preparation process and performance test of a positive electrode material, and the specific process is as follows:
[0106] (1) Dissolve 0.45 g of glyceryl monostearate in 250 mL of deionized water and anhydrous ethanol, where the volume ratio of deionized water to anhydrous ethanol is 1:3, and add 30 g of the ternary positive electrode material LiNi 0.33 Co 0.33 Mn 0.33 O2, first stir for 1 hour, and then place it in an ultrasonic disperser for ultrasonic dispersion for 0.2 hour to disperse and mix it evenly to obtain the first solution.
[0107] (2) Add 0.325 g of ammonium metavanadate and 0.367 g of diammonium hydrogen phosphate to the first solution, continue the dispersion treatment for 2 hours, and mix well to obtain a second solution.
[0108] (3) The second solution was placed in a vacuum dryer and vacuum dried at 85° C. to obtain a precursor material.
[0109] (4) The precursor material is placed in a box furnace, and the temperature is raised to 600°C at 2°C / min in a dry air atmosphere, and calcined for 4 hours so that the surface of the particles of the above-mentioned positive electrode active material is coated with VPO5. The material is naturally cooled to room temperature to finally obtain the positive electrode material.
[0110] Example 6
[0111] The purpose of this example is to verify that the coating layer of the positive electrode material of Example 1 is VO5, and no positive electrode active material and surfactant are added, and the vanadium source material and the phosphorus source material are reacted under the same conditions as in Example 1:
[0112] (1) 0.289 g of ammonium metavanadate and 0.326 g of diammonium hydrogen phosphate were dissolved in 500 mL of deionized water and anhydrous ethanol, wherein the volume ratio of deionized water to anhydrous ethanol was 1:2, dispersed for 1 hour, and mixed to obtain a mixed solution.
[0113] (2) The second solution was placed in a box dryer and vacuum dried at 90° C. to obtain a mixed powder.
[0114] (3) The mixed powder was placed in a tube furnace, heated to 600° C. at a rate of 5° C. / min in a dry air atmosphere, and calcined for 4 hours to obtain a solid material.
[0115] The XRD pattern of the solid material prepared in this example is as follows: Figure 8 As shown, it can be seen that the characteristic diffraction peak is consistent with the characteristic peak of the VPO5 standard card PDF#71-0859, indicating that the solid material prepared in this embodiment is VPO5, thus verifying that the coating layer structure of Example 1 is VPO5.
[0116] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a positive electrode material, characterized in that: The preparation method comprises: Placing the positive electrode active material, the surfactant and the solvent in a dispersing device for dispersing and mixing them uniformly to obtain a first solution; Adding the vanadium source material and the phosphorus source material to the first solution, continuing the dispersion treatment, and mixing evenly to obtain a second solution; placing the second solution in a drying device for drying to obtain a precursor material; The precursor material is placed in a high-temperature device for calcination, so that the surface of the particles of the above-mentioned positive electrode active material is coated with VPO5, and naturally cooled to room temperature to finally obtain the positive electrode material.
2. The preparation method according to claim 1, characterized in that: The positive electrode active material includes: any one of lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium iron phosphate, nickel cobalt manganese, nickel cobalt aluminum ternary material, and lithium-rich manganese-based positive electrode material; the particle size of the positive electrode active material is 0.5 μm-20 μm; The surfactant includes one or more of sodium stearate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, octadecyltrimethylammonium chloride, polyacrylamide, lecithin, glyceryl monostearate, fatty acid glyceride or polysorbate; The mass percentage of the surfactant to the mass percentage of the positive electrode active material is 0.05%-3%.
3. The preparation method according to claim 1, characterized in that: The solvent is a mixture of deionized water and anhydrous ethanol, wherein the volume ratio of deionized water to anhydrous ethanol is 1:[1-3]; The solid content of the first solution is 10 g / L-300 g / L.
4. The preparation method according to claim 1, characterized in that: The vanadium source material includes: vanadium pentoxide and / or ammonium metavanadate; the phosphorus source material includes: one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate; The molar ratio of vanadium in the vanadium source material to phosphorus in the phosphorus source material is 1:
1.
5. The preparation method according to claim 1, characterized in that: The dispersing equipment includes: one or more of an ultrasonic disperser, a mechanical stirring disperser, and a mixing disperser; and the dispersing treatment time is 12 minutes to 2 hours.
6. The preparation method according to claim 1, characterized in that: The drying equipment includes: one or more of a vacuum dryer, a box dryer, a spray dryer, a microwave dryer, an infrared dryer, a fluidized bed dryer, and an air flow dryer; The drying treatment includes: any one of normal pressure drying, reduced pressure drying, spray drying, microwave drying, and infrared drying; the temperature of the drying treatment is 40°C-120°C.
7. The preparation method according to claim 1, characterized in that: The high temperature equipment includes: any one of a tube furnace, a box furnace, and a rotary furnace; The specific conditions of the calcination are: the calcination temperature is 450°C-650°C, the heating rate is 2°C / min-10°C / min, the calcination time is 2 hours-6 hours, and the calcination atmosphere is any one of dry air, nitrogen and argon.
8. A positive electrode material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The positive electrode material includes a positive electrode active material and a VPO5 coating layer coated on the outer surface of the positive electrode active material; The VPO5 coating layer is a continuous thin film with a thickness of 2nm-5nm; The positive electrode active material includes: any one of lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium iron phosphate, nickel cobalt manganese, nickel cobalt aluminum ternary material, and lithium-rich manganese-based positive electrode material; The mass percentage of the VPO5 coating layer to the mass percentage of the positive electrode active material is 0.1%-5%.
9. A positive electrode sheet, characterized in that: The positive electrode plate comprises the positive electrode material prepared by the preparation method described in any one of claims 1 to 7 above, or the positive electrode material described in claim 8 above.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as described in claim 9 above.